Pilotage de l'irrigation par la méthode du rayonnement global - Bellouch H.; Baroud A.; Taoura M.; Sirat B. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
During last years, the region of Souss Massa has shown a great agricultural development. It contributes to more than 50 percent of citrus production and exportation and to about 80 percent for early vegetables exportations at the national level. However, this development is associated with non rational use of water resources which lead to continual decrease in ground water level, particularly in the water table of Souss where the gap is about 260 millions cubic metres per year. The use of water saving technics such as drip irrigation is the main action carried out to overcome this situation of water shortage in the region. Therefore, the area irrigated with this system is actually about 45000 hectares. In the aim of contributing to the dissemination of sustainable practices of water resources management, the ORMVA/SM, since 1996, is carrying out research development actions using the solar radian technics for crops irrigation management. The results of these researches are disseminated to growers through electronic notice bord systems.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)